3-D thermal structure and dehydration near the Chile Triple Junction and its relation to slab window, tectonic tremors, and volcanoes - Kaya Iwamoto; Nobuaki Suenaga; Shoichi Yoshioka; Francisco Ortega-Culaciati; Matthew Miller; Javier Ruiz (Geoscience Letters, 2023)
Abstract The southern Chile subduction zone is a complex tectonic environment, where the Chile Ridge, the Nazca (NZ) and Antarctic (AN) plates subduct underneath the South American (SA) plate. The intersection between the NZ, AN and SA plates is referred to as the Chile Triple Junction (CTJ). In this region, a gap, often referred to as a slab window, has been formed between the NZ and AN slabs due to the divergence in their plate motion velocities, with volcanoes existing mainly above the subducted NZ and AN plates. In this study, we constructed a three-dimensional thermomechanical model associated with simultaneous subduction of the NZ and AN plates near the CTJ. The results show that the current temperature distributions on the upper surface of the slabs are higher closer to the Chile Ridge, and the AN plate has a distribution of elevated temperatures relative to the NZ plate at the same depth due to the northward migration of the CTJ and the slower convergence rate of the AN plate. Moreover, we calculated the water content and dehydration gradient from the temperature distribution near the upper surface of the slab and discussed their relationship to the distribution of volcanoes. In the northern part of the model domain, high dehydration gradients were obtained below the volcanic chain. Therefore, we suggest that the water released from the slab and the mantle wedge decreased the melting point of the mantle wedge just above the slab and produced melts, which may have contributed to form the overlying volcanoes.